Exploring the Potential of CRISPR-Cas9 Under Challenging Conditions: Facing High-Copy Plasmids and Counteracting Beta-Lactam Resistance in Clinical Strains of Enterobacteriaceae - Tagliaferri, Thaysa Leite; Guimarães, Natália Rocha; Pereira, Marcella de Paula Martins; Vilela, Liza Figueiredo Felicori; Horz, Hans-Peter; dos Santos, Simone Gonçalves; Mendes, Tiago Antônio de Oliveira (Frontiers in Microbiology, 2020)
The antimicrobial resistance crisis urgently requires countermeasures for reducing the dissemination of plasmid-borne resistance genes. Of particular concern are opportunistic pathogens of Enterobacteriaceae. One innovative approach is the CRISPR-Cas9 system which has recently been used for plasmid curing in defined strains of Escherichia coli. Here we exploited this system further under challenging conditions: by targeting the blaTEM-1 antimicrobial resistance gene located on a high-copy plasmid (i.e. 100-300 copies/cell) and by directly tackling blaTEM-1-positive clinical isolates. Upon CRISPR-Cas9 insertion into a model strain of E. coli harbouring blaTEM-1 on the plasmid pSB1A2, the plasmid number and, accordingly, the blaTEM-1 gene expression decreased but did not get extinct in a subpopulation of CRISPR-Cas9 treated bacteria. Sequence alterations in blaTEM-1 were observed, likely resulting in a dysfunction of the gene product. As a consequence, a full reversal to an antibiotic sensitive phenotype was achieved, despite plasmid maintenance. In a clinical isolate of E. coli, plasmid clearance and simultaneous re-sensitization to five beta-lactams was possible. Reusability of antibiotics could be confirmed by rescuing larvae of Galleria mellonella infected with CRISPR-Cas9-treated E. coli, as opposed to infection with the unmodified clinical isolate. The drug sensitivity levels could also be increased in a clinical isolate of E. hormaechei and to a lesser extent in K. variicola, both of which harboured additional resistance genes affecting beta-lactams. The data show that targeting drug resistance genes is encouraging even when facing high-copy plasmids. In clinical isolates, the simultaneous interference with multiple genes mediating overlapping drug resistance might be the clue for successful phenotype reversal.